Lebensformen 2000 : Eine Ausstellung Bonner Künstlerinnen und Künstler : Bonner Kunstwoche 1989. (Bonn : Künstlerforum Bonn, 1989)
Altrock-Lutterjohann, Monika ; B'ay, Eve ; Bille, Elisabeth ; Bingler, Kurt-Otto ; Bongers, Jürgen ; Brunetti, Carlotta ; Cohen-Or, Beni ; Damosy, Géza ; Ebener, Wolf ; Eichner, Hellmuth ; Frings, Christiane ; Gabrien, Peter K. ; Glock, Ilsetraud ; Görtemaker, Elke ; Hanke, Christoph ; etc.
Lebensformen 2000 : Eine Ausstellung Bonner Künstlerinnen und Künstler : Bonner Kunstwoche 1989, Künstlerforum Bonn, 1989
boek